Risk of bleeding and adverse outcomes predicted by thromboelastography platelet mapping in patients taking clopidogrel within 7 days of non-cardiac surgery. Issue 11 (4th August 2014) - Kasivisvanathan, R; Abbassi-Ghadi, N; Kumar, S; Mackenzie, H; Thompson, K; James, K; Mallett, S V
Abstract: Background: Patients often fail to stop clopidogrel appropriately before non-cardiac surgery. Thromboelastography platelet mapping (TEG-PM) can be used to measure the percentage adenosine 5′-diphosphate platelet receptor inhibition (ADP-PRI) by clopidogrel in these patients. Methods: This prospective case–control study investigated the risk of bleeding in patients who had taken clopidogrel within 7 days of scheduled operation. Patients underwent TEG-PM to stratify their bleeding risk. Low-risk (ADP-PRI below 30 per cent) and urgent priority high-risk (ADP-PRI 30 per cent or more) patients proceeded to surgery. The outcomes of these patients were compared with those of matched controls. Regression analysis, with bootstrapping validation, was used to identify independent risk factors for bleeding and an optimal cut-off value of ADP-PRI for cancellation of surgery. Results: From May 2008 to October 2013, 182 patients failed to discontinue clopidogrel. No correlation was observed between duration of clopidogrel omission and percentage ADP-PRI; 112 low-risk and 19 high-risk patients proceeded to surgery. High-risk patients had significantly greater intraoperative packed red blood cell (PRBC) transfusion in comparison with their matched controls, and a strong positive correlation between percentage ADP-PRI and units of intraoperative PRBCs transfused ( r = 0·749, 95 per cent confidence interval (c.i.) 0·410 to 0·940; P < 0·001). Percentage ADP-PRI was the only independent risk factor for intraoperative PRBC transfusion (odds ratio 1·07, 95 per cent c.i. 1·02 to 1·13; P = 0·005). Conclusion: An objective measure of platelet inhibition with TEG-PM, using an ADP-PRI cut-off of 34 per cent, can be used to prevent unnecessary cancellations, while minimizing patient risk. Abstract : For those who forget to stop clopidogrel